2017
DOI: 10.1021/acs.organomet.7b00091
|View full text |Cite
|
Sign up to set email alerts
|

C–H Activation of Cp* Ligand Coordinated to Ruthenium Center: Synthesis and Reactivity of a Thiolate-Bridged Diruthenium Complex Featuring Fulvene-like Cp* Ligand

Abstract: In the presence of weak base Et 3 N, the interaction of [Cp*Ru(μ-η 2 :η 4 -bdt)RuCp*] (1, Cp* = η 5 -C 5 Me 5 ; bdt = benzene-1,2-dithiolate) with 2 equiv of Fc•PF 6 resulted in facile C−H activation of one methyl group in coordinated Cp* to give a diruthenium complex with a fulvene-like Cp* ligand, [(η 5 :η 1 -C 5 Me 4 CH 2 )Ru(μ-η 2 :η 4 -bdt)RuCp*][PF 6 ] (2[PF 6 ]), in which the fulvene-like Cp* moiety is best described as an η 5 :η 1 -tetramethylfulvene ligand based on 1 H NMR and 13 C NMR spectroscopic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 81 publications
2
3
0
Order By: Relevance
“…This process requires to overcome an energy barrier of 17.0 kcal·mol –1 , dictated by transition structure TS-AB , which is feasible under the reaction conditions (RT and 333 K). Remarkably, within TS-AB , the Cp* ligand changes its coordination mode form η 5 to η 1 , as we previously proposed for the related complex [Cp*IrCl­{(MeIm) 2 CHCOO}] and which is enabled by the flexibility in the coordination modes of the pentamethylcyclopentadiene ligand. The next step involves the hydrosilane activation through a ligand-assisted Si–H bond cleavage process, which is in line with other activation proposals for similar Ir-based catalysts. , This step leads to intermediate C and involves the formation of a Si–O bond in the carboxylate moiety and a Rh–H bond. This species has a relative energy of 0.0 kcal·mol –1 , being 10.1 kcal·mol –1 more stable than B as a consequence of the high oxophilicity of silicon, which favors the formation of the Si–O bond.…”
Section: Results and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This process requires to overcome an energy barrier of 17.0 kcal·mol –1 , dictated by transition structure TS-AB , which is feasible under the reaction conditions (RT and 333 K). Remarkably, within TS-AB , the Cp* ligand changes its coordination mode form η 5 to η 1 , as we previously proposed for the related complex [Cp*IrCl­{(MeIm) 2 CHCOO}] and which is enabled by the flexibility in the coordination modes of the pentamethylcyclopentadiene ligand. The next step involves the hydrosilane activation through a ligand-assisted Si–H bond cleavage process, which is in line with other activation proposals for similar Ir-based catalysts. , This step leads to intermediate C and involves the formation of a Si–O bond in the carboxylate moiety and a Rh–H bond. This species has a relative energy of 0.0 kcal·mol –1 , being 10.1 kcal·mol –1 more stable than B as a consequence of the high oxophilicity of silicon, which favors the formation of the Si–O bond.…”
Section: Results and Discussionsupporting
confidence: 77%
“…Remarkably, within TS-AB the Cp* ligand changes its coordination mode form  5 to  1 , as we previously proposed for the related complex [Cp*IrCl{(MeIm)2CHCOO}], 22 and which is enabled by the flexibility in the coordination modes of the pentamethylcyclopentadiene ligand. 32,33,34 The next step involves the hydrosilane activation through a ligand assisted Si-H bond cleavage process, in line with other activation proposals for similar Ir-based catalysts. 29,35 This step leads to intermediate C and involves the formation of a Si-O bond in the carboxylate moiety and a Rh-H bond.…”
Section: Resultssupporting
confidence: 58%
“…On rare occasions it can be a participant in the chemistry exhibited by its molecular scaffolds while remaining coordinated to the metal center. For instance, under a variety of experimental conditions, the C–H bond activation of a methyl group in coordinated Cp* ligands was shown to result in the formation of either η 2 :η 4 or η 1 :η 5 tetramethylfulvene-like ligands via H atom abstraction . Recently, it has also been reported that treatment of 18e Cp*Rh­(bpy) [bpy = κ 2 -2,2′-bipyridine] with a protonic acid initially affords the 16e pentamethylcyclopentadiene-containing cation, [(η 4 -Cp*H)­Rh­(bpy)] + , which is believed to result from the C–H bond-forming reductive elimination from the transient rhodium hydrido complex, [Cp*Rh­(bpy)­H] + . , Even rarer are the cases in which Cp*H is liberated as the free diene, having been previously reported for the solvent-induced elimination of Cp*H from [Cp*Ir­(H) 3 (PPh 3 )] + and the phosphine-induced liberation from Cp*Rh­(H) 2 (PMe 3 ) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…15 The potential formation of a Rh I (η 4 -tetramethylfulvene) intermediate was postulated as one of the key steps in the latter reaction, which was also identified in a Diels−Alder reaction with isoprene for a bipyridyl Rh(Cp*) complex. 16 The activation of the Cp* ligand was also reported in the syntheses of diruthenium complexes, 10 dehydrofluorinative coupling reactions, 17 and other types of cyclometalation reactions. 14,18,19 Notably, in all these cases with polydentate all-carbon donoratom ligands, at least one of the coordination sites of the Rh center was occupied by a heteroatom or other carbon-based ligand systems.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Rh-catalyzed reactions have attracted significant interest due to the wide range of applications in synthetic chemistry. In particular, Rh-catalyzed C–H bond functionalization has been used for the atom-economical construction of C–C and C–heteroatom bonds in a diverse range of chemical transformations. Rh III and Ir III compounds bearing η 5 -pentamethylcyclopentadienyl (Cp*) and N -heterocyclic carbene (NHC) ligands have widely been investigated as catalysts, where the metal center is involved in the catalytic activity while the Cp* and NHC ligands often act as spectator ligands and rarely undergo any transformations during a catalytic reaction cycle.…”
Section: Introductionmentioning
confidence: 99%